THE LIFE HISTORY AND FEEDING HABITS OF A TRIPOD FISH (TRIACANTHUS BREVIROSTRIS TEMM. & SCHLEG.) OF THE INDIAN SEA - Dr. M.D. K. KUTHALINGAM,M. Sc Ph. D., F. A.Z (BRIN Publishing (Penerbit BRIN), 1959)
-